Perspektif etis, yuridis dan teologis terhadap perkawinan sejenis - Tjutjun Setiawan; Ferry Simanjuntak; Yanto Paulus Hermanto (TE DEUM (Jurnal Teologi dan Pengembangan Pelayanan), 2021)
Homosexuals hope that society will accept their existence and no longer gives negative stigma. They also hope to receive the same treatment as heterosexuals, where they can marry their partners. This study discusses ethical, juridical and theological perspectives on same-sex marriage. This research uses a qualitative method with a literature study approach. Through this research, the writer hopes that the church has an understanding and knows how to behave towards homosexuals and their demands to be able to do marriages with same-sex partners. The author also hopes that homosexuals can realize and repent that their behavior is wrong and ethically deviant, violates juridical rules and even their behavior is a sin before God.